The nylon balloon for xenon loaded liquid scintillator in KamLAND-Zen 800 neutrinoless double-beta decay search experiment. (9th August 2021) - Gando, Y.; Gando, A.; Hachiya, T.; Hayashida, S.; Hosokawa, K.; Ikeda, H.; Mitsui, T.; Nakada, T.; Obara, S.; Ozaki, H.; Shirai, J.; Ueshima, K.; et al.
Abstract: The KamLAND-Zen 800 experiment is searching for the neutrinoless double-beta decay of 136 Xe by using 136 Xe-loaded liquid scintillator. The liquid scintillator is enclosed inside a balloon made of thin, transparent, low-radioactivity film that we call Inner Balloon (IB). The IB, apart from guaranteeing the liquid containment, also allows to minimize the background from cosmogenic muon-spallation products and 8 B solar neutrinos. Indeed these events could contribute to the total counts in the region of interest around the Q-value of the double-beta decay of 136 Xe. In this paper, we present an overview of the IB and describe the various steps of its commissioning minimizing the radioactive contaminations, from the material selection, to the fabrication of the balloon and its installation inside the KamLAND detector. Finally, we show the impact of the IB on the KamLAND background as measured by the KamLAND detector itself.